Effect of Inoculum Dose and Fermentation Time on Enzyme Activity and Nutrients of Palm Kernel Cake Fermented with Sclerotium rolfsii Powder Inoculum - Fajrona, Kadran; Rizal, Yose; Mirnawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The study aimed to determine the inoculum dose and fermentation time of palm kernel cake with Sclerotium rolfsii powder inoculum on the enzyme activity of cellulase, mannanase, crude protein, and crude fiber. This study used an experimental method with a completely randomized design of a factorial 3x3 with two replications. Factor A is the inoculum dose consisting of A1: 6%, A2: 8%, and A3: 10%. Factor B is the fermentation time, which consists of B1: 5 days, B2: 7 days, and B3: 9 days. The measured parameters were cellulase and mannanase enzyme activity, crude protein, and fiber content. The data obtained were analyzed using ANOVA and continued with Duncan's multiple range test. The results show that the inoculum dose and fermentation time significantly affect (P<0.01) cellulase and mannanase enzyme activity, crude protein, and crude fiber content. The use of an inoculum dose of 8% and a fermentation period of 7 days gave the best results with an average cellulase enzyme activity of 26.77 U/ml, mannanase enzyme activity of 27.35 U/ml, crude protein of 24.07 U/ml and crude fiber of 19.26%.